Circulação de crianças e adolescentes no centro de São Paulo: entre liberdades e controles - Mendes, Gabriel Rocha Teixeira (2019)
Children and adolescents living in the street situation circulate through public service in a move that evidence tensions between protection and rights guarantee, for a side; regimentation and guardianship of their liberties, for another. Thus, the objective of this research consists to characterize and analyze the trajectories of children and adolescents, in the streets of center of São Paulo, as a way to problematize their meetings with the public policies, especially those that respond to the use of alcohol and other drugs. For both, cartography the movement of children and adolescents, highlighting the two different modes of life: a boy who lives “alone” in the vicinity of the Cracolândia; that of boys and girls who live in band around the Praça da Sé. The itineraries of the children were drawn from their meetings (and disagreements) with the team of a mental health service, the Center for Psychosocial Care for Children and Adolescents (CAPSij), when traveling to the greatest vulnerability areas, what is called “CAPS on the Street”. Using contributions of Michel Foucault and micropolitical in Deleuze and Guattari, analyzed the tensions between the modes of government realized by the different policies (health, social assistance and security) and the children nomadism, evidencing the singular modes of children's lives in the unprecedented uses of the social policies offered to them and the challenges they present to public policies